The Role of Hyponatraemia Before Surgery in Patients With Radical Resected Pancreatic Cancer. (June 2020) - Berardi, Rossana; Rinaldi, Silvia; Belfiori, Giulio; Partelli, Stefano; Crippa, Stefano; Torniai, Mariangela; Falconi, Massimo
Objectives: Hyponatraemia represents a negative prognostic factor in patients with cancer. The aim of this study was to assess, for the first time, the role of hyponatraemia in patients undergoing radical surgery for pancreatic ductal adenocarcinoma. Methods: A total of 89 patients with stage I-III pancreatic ductal adenocarcinoma underwent radical surgery between November 2012 and October 2014. Relapse-free survival (RFS) and disease-specific survival (DSS) were estimated using Kaplan-Meier method. A Cox regression model was carried out for univariate and multivariate analyses. Fisher exact test was used to estimate correlation between variables. Results: In total, 12 patients (14%) presented with hyponatraemia at diagnosis. The median DSS was 20 months in patients with hyponatraemia and not reached in patients with eunatraemia ( P < .1073), while a statistical significant difference was observed in terms of median RFS (10 months vs 17 months, respectively; P = .0233). Considering clinical features (hyponatraemia, smoke and alcoholic habit, diabetes, pain, and jaundice), patients with 4 or more of these factors had a worse prognosis (mDSS: 30 months vs not reached; hazard ratio [HR]: 0.40, 95% confidence interval [CI] = 0.16-0.80; P = .0120). Conclusions: The presence of hyponatraemia and its prompt correction at the diagnosis time should be considered for the correct management of patients with pancreatic carcinoma.